The girl who kicked the hornet's nest ebook - Larsson, Stieg (Millennium, 2010)
#1 NATIONAL BESTSELLER • In this “thoroughly gripping” ( New York Times ) continuation of the Girl with the Dragon Tattoo series, Lisbeth Salander lies in critical condition in a Swedish hospital, a bullet in her head. But she's fighting for her life in more ways than one: if and when she recovers, she'll stand trial for three murders. • Also known as the Millennium series In the next installment of the Millennium series, with the help of Mikael Blomkvist, Salander will need to identify those in authority who have allowed the vulnerable, like herself, to suffer abuse and violence. And, on her own, she'll seek revenge—against the man who tried to kill her and against the corrupt government institutions that nearly destroyed her life. Look for the latest book in the Girl with the Dragon Tattoo series, The Girl in the Eagle's Talons , coming soon!